Novel colloidal poly(MA-alt-1-dodecene)-g-PEO/ODA-MMT/AgNPs nanohybrid composites as antimicrobial, antifungal and anticancer platforms - D. Demircan; Z. M. O. Rzayev; K. Salimi (eXPRESS Polymer Letters)
This work presents a new approach to synthesize the colloidal ODA-MMT-poly(maleic anhydride-alt-1-dodecene)-g-α,ω-methoxyhydroxyl-PEO/silver nanoparticles (AgNPs) nanohybrid composites (NHC) using the following synthetic pathways: (1) complex-radical alternating copolymerization of maleic anhydride with 1-dodecene α-olefin comonomer, (2) grafting of PEO onto alternating copolymer through esterification, (3) intercalating a copolymer-g-PEO between organoclay layers via complex formation of maleate carboxyl with octadecyl amine, and (4) in situ generation of AgNPs in polymer nanocomposite by annealing method under vacuum. The obtained multifunctional NHCs with different contents of AgNPs were characterized by UV spectroscopy, ζ-potential and size analysis methods. It was demonstrated that annealing of the colloidal NHC is accompanied with in situ generation of stable and partially protonated AgNPs due to specific reducing and stabilizing effects of multifunctional matrix polymer contained positively charged reactive and bioactive sites. Antibacterial and antifungal activities against Gram-negative and Gram-positive bacteria and fungal microorganism were investigated. The cytotoxic, apoptotic and necrotic effects in NHC/L929 fibroblast cells systems were evaluated. The synthesized watersoluble, biocompatible, and bioactive colloidal NHCs are promising candidate for a wide-range of applications in air filtration, food packaging systems, bioengineering, especially in tissue regeneration and nanomedicine.